Pengenalan Pola Untuk Deteksi Uang Koin - Nesi Syafitri (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2011)
AbstractPattern Recognition (Pattern Recognition) is one branch of Artificial Intelligence. Pattern recognition is a grouping of numeric and symbolic data (including images) automatically by machine (computer). The purpose of grouping is to recognize objects based on the characteristics possessed by the object / pattern. A pattern is a defined entity and can be identified by its characteristics (features). These features are used to distinguish a pattern with other patterns. In this research the pattern to be used is silver and gold coins. The features that can be used is the color and area characteristics. Stages that must be passed to classify these coins there are 2 (two) stages: first is the training stage and the second is the recognition stage. In the training phase starts from feature selection process and the learning process. At the recognition  phase begins from preprocessing, feature extraction process and the final process of pattern classification Results of pattern recognition coins can be used to separate groups of coins, determine the value of coins from each group and calculate the total value of these coins exist. Keywords: Pattern Recognition, Preprocessing, feature extraction, classification